2013
DOI: 10.1038/ismej.2012.161
|View full text |Cite
|
Sign up to set email alerts
|

Coral and macroalgal exudates vary in neutral sugar composition and differentially enrich reef bacterioplankton lineages

Abstract: Increasing algal cover on tropical reefs worldwide may be maintained through feedbacks whereby algae outcompete coral by altering microbial activity. We hypothesized that algae and coral release compositionally distinct exudates that differentially alter bacterioplankton growth and community structure. We collected exudates from the dominant hermatypic coral holobiont Porites spp. and three dominant macroalgae (one each Ochrophyta, Rhodophyta and Chlorophyta) from reefs of Mo'orea, French Polynesia. We charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
279
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 218 publications
(324 citation statements)
references
References 102 publications
18
279
3
Order By: Relevance
“…The current study confirms and extends earlier findings (27) by demonstrating similar correlations between benthic community composition and the enrichment of specific microbial taxa on coral reefs in situ (Table 1). Consistent with the effects of individual exudates, high coral cover was associated with higher abundances of Alphaproteobacteria, whereas the abundant fleshy macroalgae at Tabuaeran and Teraina were accompanied by more Gammaproteobacteria (e.g., Enterobacteriales and Pseudomonadales).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The current study confirms and extends earlier findings (27) by demonstrating similar correlations between benthic community composition and the enrichment of specific microbial taxa on coral reefs in situ (Table 1). Consistent with the effects of individual exudates, high coral cover was associated with higher abundances of Alphaproteobacteria, whereas the abundant fleshy macroalgae at Tabuaeran and Teraina were accompanied by more Gammaproteobacteria (e.g., Enterobacteriales and Pseudomonadales).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the microbial communities sampled on these reefs reflected selection by the adjacent benthic macroorganisms, as evidenced by the differences between reef-associated bacterioplankton communities and open ocean communities (26). There is evidence that reef-associated communities undergo selection in shallow reef environments by the locally available labile organic matter exuded by the benthic organisms (27). For example, in an empirical study, Nelson et al demonstrated that exudates collected from coral and macroalgae selectively fostered growth of distinct bacterioplankton communities (27).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…DDAM predicts that stressors such as overfishing and eutrophication release turf and fleshy macroalgae from grazing control, leading to increased release rates of labile DOC. DOC stimulates heterotrophic microbial growth [18][19][20][21], some of which are opportunistic coral pathogens [22]. These pathogens kill corals and create more space for the algae.…”
Section: Introductionmentioning
confidence: 99%